Compliance and Impact of CSR Regulations on Working Capital Management : A Semantic Analysis of Global Financial Strategies - Deni Sunaryo; Syamsudin Syamsudin; Feldi Ilahi; Agnes Alfiyani; Daud Bintang Mustafani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study examines the impact of Corporate Social Responsibility (CSR) regulations on working capital management in a global context, considering a variety of regulations and practices across different countries. Utilizing a semantic literature review approach, this article explores how CSR interacts with corporate financial strategies, specifically in managing working capital. Findings suggest that stringent CSR regulations often motivate companies to adopt more efficient working capital practices, which not only comply with CSR standards but also enhance financial performance. This research identifies variations in the adaptation of working capital practices influenced by differences in CSR policies across regions and industries. Through an extensive literature analysis, this study provides new insights into the dynamic relationship between CSR regulations and working capital management, and proposes strategies for companies to synchronize CSR compliance with optimal financial achievement.